Analysis of the Effectiveness of Official Travel and Work Discipline on the Achievement of Work Outcomes and Its Implications for Employee Performance - M.Lutfi Firmansyah; Vip Paramarta; Sri Rochani Mulyani (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to analyze the effect of official travel effectiveness and work discipline on work achievement and its implications for employee performance at the Department of Agriculture, Food Security, and Fisheries of Tasikmalaya Regency. The background of this study is based on the high intensity of official travel activities and the suboptimal level of employee discipline, which are suspected to affect productivity and organizational performance. This research employed a quantitative method with descriptive and verificative approaches. The number of respondents was 76 employees, determined using the Slovin technique. Data were analyzed using path analysis to examine both direct and indirect relationships among variables. The results indicate that the effectiveness of official travel and work discipline have a significant effect on work achievement, with coefficients of 0.327 and 0.416, respectively. Work achievement also has a significant effect on employee performance, with a coefficient of 0.495. The indirect effect of official travel effectiveness on employee performance through work achievement is 0.219, while the direct effect is 0.104. The total contribution of the model to employee performance is 81.9% (R² = 0.819), with a residual error value of 0.43. The study concludes that effective management of official travel activities and consistent enforcement of work discipline play an important role in improving work achievement and employee performance.